2004
DOI: 10.1002/lsm.20040
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic effects of anthracyclin derivatives on squamous cell carcinoma cell lines of the head and neck

Abstract: These results revealed that the above mentioned cytostatics could be considered as possible alternative photosensitizer for photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Lippert et al 8 reported on the effect of combined application of ADR and laser light irradiation on various squamous cell carcinoma cell lines and found a synergetic effect by a factor of 2, which was attributed to photodynamic activity of ADR. Lou et al 9 reported on the reversal of the resistance of breast cancer cells to ADR by the application of the so-called photochemical internalization (PCI) method 10 , which involves release of endocytosed macromolecular agents into the cytosol after photochemically-induced rupture of the endocytic vesicles.…”
Section: Discussionmentioning
confidence: 98%
“…Lippert et al 8 reported on the effect of combined application of ADR and laser light irradiation on various squamous cell carcinoma cell lines and found a synergetic effect by a factor of 2, which was attributed to photodynamic activity of ADR. Lou et al 9 reported on the reversal of the resistance of breast cancer cells to ADR by the application of the so-called photochemical internalization (PCI) method 10 , which involves release of endocytosed macromolecular agents into the cytosol after photochemically-induced rupture of the endocytic vesicles.…”
Section: Discussionmentioning
confidence: 98%
“…9,33,35,37,40,46,48,52,55,66,67 Other porphyrin platform PSs such as PAD-S31, HpD, Photofrin II, Photosan III, hydroxy purpurin, mTHPP, and Protoporphyrin IX (PpIX) were studied in some articles. [56][57][58][59]62 Chlorophyll platform PSs, including chlorin e6, NPe6, chlorin p6, mTHPC, pheophorbide a, and 9-hydroxy pheophorbide a were applied in other studies . 29,31,38,39,41,43,49,54 One study used 15(1)-hydroxypurpurin-7-lactone ethyl methyl diester as a PS, which was isolated for the first time from an Araceae plant and referenced to Pha.…”
Section: Photosensitizermentioning
confidence: 99%
“…Some studies used only one concentration, 33,[38][39][40]43,45,[47][48][49]51,55,56,58,59,66,67 while others evaluated the effect of different concentrations on their cell lines. 9,23,[29][30][31][32]34,36,37,41,42,44,46,50,53,54,57,[60][61][62][63][64][65]68 Most studies showed that the results were dependent on concentrations. 9,23,[29][30][31]34,36,41,42,44,46,…”
Section: Photosensitizermentioning
confidence: 99%
“…The author also compared different anti-cancer agents combined with LITT ablation for inoperable esophageal cancer and reported that cisplatin (CDDP) was more effective than anthracyclines or cyclophosphamide when combined with Nd:YAG laser. However, other studies done in children with retinoblastoma found that Adriamycin derivatives were more cytotoxic in tumors after laser photo-thermal activation (Andreoni et al, 1991;Gallie et al, 1996;Lippert et al, 2004;Lueder and Goyal, 1996;Murphree et al, 1996). From a historical perspective, initial work on chemotherapy and lasers was reported in clinical models investigating combined palliative therapy for inoperable esophageal cancers.…”
Section: Clinical Relevance Of Laser and Cisplatin In Photo Chemotherapymentioning
confidence: 99%